Motivational Profile And Business Creation: Case Of Entrepreneurs In Sfax - Abdennadher, Sarhan; Boudabbous, Sami (Entrepreneurship Undergraduate Program at Amkop Business School, 2024)
Entrepreneurship has nowadays become a priority for governments seeking to raise the level and pace of business creation given its many positive socio-economic benefits. Efforts have been made to promote, encourage and support entrepreneurs in their journeys. However, in the absence of entrepreneurial motivation and a favorable environment, all efforts will not have an impact. Knowledge of the motivational profile of the business creator thus becomes a key factor prior to the success of support programs and measures taken to promote entrepreneurship and business creation. It is in this context that this research work takes place, which aims to explore the motivations for business creation among entrepreneurs in Sfax (Tunisia). The results we achieved show the coexistence of several types and levels of entrepreneurial motivations. These motivations concern the entrepreneur himself, his direct entourage as well as the characteristics of his environment. Keywords: entrepreneurial motivation, business creation, entrepreneurs, Sfax